Biology Teacher Creativity at SMKN Maros Regency in Solving Online Learning Problems by Utilizing E-Learning - Lestari, Pertiwi Indah; Nur, Rizki Amalia; Riyanti, Rika (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This study employed a qualitative method to determine the teachers’ creativity in utilizing e-learning media in online learning. This study implemented a survey approach that involved theories, relevant evidence, and existing facts by emphasizing the structural model (path) of the relationship between the variables studied. The subjects of this study were 20 students of SMKN 2 Maros and four homeroom teachers. The data collecting technique used by the researchers were questionnaires and online interviews. The data analysis technique referred to by Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. Based on research, the teachers' creativity at SMKN 2 Maros in utilizing e-Learning was 82.5 and 85 in the high creativity category. Therefore, the creativity in using e-Learning during the online learning process was high.ABSTRAK: Penelitian ini merupakan penelitian kualitatif yang bertujuan untuk mengetahui kreativitas guru dalam pembelajaran daring dengan memanfaatkan media e-learning dalam pembelajaran. Penelitian ini menggunakan pendekatan survey yang melibatkan teori, bukti yang relevan, fakta dan kenyataan yang ada pada penekanan model struktural (jalur) hubungan antar variabel yang dikaji. Subjek penelitian ini adalah 20 siswa SMKN 2 Maros dan 4 orang guru kelas. Teknik yang digunakan peneliti dalam penelitian ini adalah dengan cara angket, wawancara secara daring. Teknik analisis data yang digunakan yaitu reduksi data Miles and Huberman yaitu, data reduction, data display, dan conclusion drawing/verivication. Berdasarkan penelitian yang telah dilaksanakan kreativitas guru SMKN 2 Maros dalam memanfaatkan media e-Learning termasuk dalam kriteria kreativitas yang tinggi dengan skor 82,5 dan 85, artinya kreativitas guru dalam memanfaatkan media e-Learning selama proses pembelajaran daring tergolong tinggi.